Staphylococcus aureus: resistência de virulência e tipagem de MRSA pelas técnicas de MLST e spa typing - Souza, Camila Sena Martins de [UNESP] (2014)
Staphylococcus aureus is distinguished by its high pathogenicity and frequency, allowing that this agent is capable of producing diseases in both healthy individuals and immunocompromised due to its easy dissemination. The aim of this work was to characterize the distribution of clones of S. aureus sensitive and resistant (MSSA/MRSA) in 50 isolates from patients with skin infections of Section of Dermatology of the University Hospital of the Botucatu Medical School Hospital of the (FMB), 50 isolates of elderly residents of nursing homes of Bauru and 50 isolates from inmates of Detention Center of Avare. The isolates of S. aureus were subjected to the technique of E-test for determination of Minimum Inhibitory Concentration (MIC). To determine the virulence profile and oxacillin resistance in 150 isolates of S. aureus was used Polymerase Chain Reaction (PCR) for the detection of mecA gene, staphylococcal cassette chromosome mec (SCCmec), genes encoding enterotoxins (sea, seb and sec-1), exfoliative toxins A and B (eta e etb), toxic shock syndrome toxin 1 (tst), Panton-Valentine leukocidin (lukS-PV and lukF-PV), alpha and delta hemolysin (hla and hld) and biofilm (icaA and icaD). The clonal profile of MRSA and MSSA isolates were characterized by Pulsed Field Gel Electrophoresis (PFGE), and MRSA clones were subjected to molecular typing Multilocus Sequence Typing (MLST) and spa typing. The results revealed a higher prevalence of MRSA in institutional settings, besides having MIC90 64μg/mL for oxacillin and MIC90 > 256 mg/mL for clindamycin. Of the 150 samples of S. aureus studied, 20 (13.3%) were mecA carriers, being detected seven isolates harboring SCCmec type IV nine carrying the SCCmec type II, only one isolate carrying the SCCmec type I and 3 isolates were not typed by the protocol used. Among the virulence factors, enterotoxin A was the most prevalent in all sources. Is important to note, 10% of isolates from Center Resocialization ...